2015
DOI: 10.4172/2155-9600.1000381
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chronic Under Nutrition (Stunting) Among Children Aged 6-23 Months in Kemba Woreda, Southern Ethiopia: A Community Based Cross-Sectional Study

Abstract: Background: Stunting is a public health problem in developing countries. Stunting (deficit in height/length for age of at least-2 Z score) affects close to 195 million children under five years of age in the developing world. Chronic under nutrition is a major cause of disability preventing children who survive from reaching their full developmental potential. Objective: To assess chronic under nutrition (Stunting) and associated factors among Children aged 6-23 months in Southern Ethiopia. Methods: Community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Although stunting often begins in utero, several research studies have identified socio-demographic, socioeconomic [11][12][13][14][15][16], environmental [17,18], dietary [12,18,19], parasitic infection and other related illness [11,20], and psychological [19] correlations with stunting. One of the psychological factors that might be associated with children stunting is unintended pregnancy, either unwanted (the parent did not desire any or any more children) or mistimed (the pregnancy occurred earlier than desired) [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although stunting often begins in utero, several research studies have identified socio-demographic, socioeconomic [11][12][13][14][15][16], environmental [17,18], dietary [12,18,19], parasitic infection and other related illness [11,20], and psychological [19] correlations with stunting. One of the psychological factors that might be associated with children stunting is unintended pregnancy, either unwanted (the parent did not desire any or any more children) or mistimed (the pregnancy occurred earlier than desired) [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Study based in India showed that maternal age is positively associated with stunting among children (58), while some studies showed that stunting is inversely related with maternal age (63,64). Many studies have documented that with the increase of maternal education, the chances of stunting decrease among children (44,54,(65)(66)(67)(68). Mother's body mass index that is negatively associated with stunting among children, also another important risk factor of stunting among children as evidenced by the previous studies (28,44,67).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…Much literature exists on the reasons behind the stunting decline in Ethiopia, and findings point to several key drivers: parental education ( 16–33 ); health care interventions, such as delivery by a skilled birth attendant (SBA) ( 17 , 34–36 ), antenatal care ( 16 , 17 , 26 , 34 , 37–44 ), and postnatal care ( 45 , 46 ); improvements in water, sanitation, and hygiene (WASH), including access to improved water sources ( 21 , 32 , 37 , 39 , 40 , 45 , 47–58 ), reduced distance to fetch water ( 59 ), access to improved sanitation ( 17 , 20 , 21 , 23 , 27 , 29 , 39 , 40 , 45 , 51 , 60–63 ), and reductions in open defecation ( 19 , 27 ); and child feeding indicators ( 19 , 30 , 37 , 38 , 60 , 64–70 ) ( Panel 1 , Supplemental Appendix 2 ) ( 16–98 , 99–118 , 119–142 ). Although we found a wealth of national and subnational studies exploring factors related to stunting in Ethiopia, the overwhelming majority were cross-sectional in design which precludes causality.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies in our review found that childhood immunizations have a protective effect against stunting outcomes ( 28 , 39 , 40 , 50 , 93–95 ), although some found no association ( 23 , 38 , 45 , 51 , 97 , 98 ). Health care interventions such as delivery by an SBA ( 17 , 34–36 ), antenatal care ( 16 , 17 , 26 , 34 , 37–44 ), and postnatal care ( 45 , 46 ) have been found to be associated with reduced stunting outcomes in most studies, although some found no association ( 16 , 19 , 22 , 27 , 30 , 35 , 42 , 45 , 49 , 60 , 64 , 71 , 86 ). Vitamin A supplementation is a promising initiative shown to be associated with a decreased risk of stunting, although variation in findings exists ( 40 , 60 , 61 , 67 , 99–102 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation